The prevalence of traumatic brain injury (TBI) and an investigation of behavioural and executive functioning outcomes (among those who have sustained TBIs) in a sample of male young offenders - Ockhuizen, Helen Ju-Reyn (Department of Psychology, 2015)
Includes bibliographical references.